Limiting incorrect equations in the Hilbert space - Pogorui , A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
The behavior of the solution of a limit-ill-posed problem on fixed compacta is investigated for integral operators, acting in a Hilbert space.